Chemotherapeutic agent doxorubicin alters uterine gene expression in response to estrogen in ovariectomized CD-1 adult mice†. Issue 4 (17th December 2018) - Andersen, Christian Lee; Liu, Mingjun; Wang, Zidao; Ye, Xiaoqin; Xiao, Shuo
Abstract: Chemotherapy can potentially impair fertility in premenopausal cancer patients. Female fertility preservation has been mainly focused on the ovarian aspects and benefited greatly from assisted reproductive technologies, such as in vitro fertilization (IVF). The rate-limiting step for the success of IVF is embryo implantation in the uterus. Doxorubicin (DOX) is a widely used chemotherapeutic agent with ovarian toxicity. It remains unknown if the uterus is a direct target of DOX. To circumvent the indirect uterine effect from ovarian toxicity of DOX and to investigate potential long-term impact of DOX on the uterus, young adult ovariectomized CD-1 mice were given an intraperitoneal injection once with PBS or DOX (10 mg/kg, a human relevant chemotherapeutic dose), and 30 days later, each set of mice was randomly assigned into three groups and subcutaneously injected with oil, 17β-estradiol (E2, for 6 h), and progesterone (P4, for 54 h), respectively. Uterine transcriptomic profiles were determined using RNA-seq. Principal component analysis of the uterine transcriptomes revealed four clusters from the six treatment groups: PBS-oil & DOX-oil, PBS-P4 & DOX-P4, PBS-E2, and DOX-E2, indicating that DOX treatment did not affect the overall uterine transcriptomic profiles in the oil and P4-treated mice but altered uterine responses to E2 treatment. DAVID analysis indicated that the top-affected gene cluster was "Glycoprotein". These data demonstrate that DOX can directly target the uterus and has a long-term impact on uterine responses to E2. Abstract : Our finding that a single dose of doxorubicin relevant to human treatment level can change uterine gene expression in response to estrogen in ovariectomized mice one month later indicates that the uterus is a direct target of doxorubicin and doxorubicin has a long-term impact on the uterus.